1998
DOI: 10.1063/1.556029
|View full text |Cite
|
Sign up to set email alerts
|

Revised Formulation for the Refractive Index of Water and Steam as a Function of Wavelength, Temperature and Density

Abstract: Schiebener et al. published a formulation for the refractive index of water and steam in 1990 ͓J. Phys. Chem. Ref. Data 19, 677 ͑1990͔͒. It covered the ranges 0.2 to 2.5 m in wavelength, Ϫ12 to 500°C in temperature, and 0 to 1045 kg m Ϫ3 in density. The formulation was adopted by the International Association for the Properties of Water and Steam ͑IAPWS͒ in 1991. In the present article, the data, after conversion to ITS-90, have been refitted to the same functional form, but based on an improved equation of st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
188
0
3

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 338 publications
(212 citation statements)
references
References 12 publications
17
188
0
3
Order By: Relevance
“…In order to validate the high pressure cell and the measurement technique, we measured the refractive index of three different pure fluids (toluene, hexane, and water, which refractive indices as a function of pressure are given in literature [29][30][31] ) as a function of pressure in the range from atmospheric pressure up to 50 MPa. In Fig.…”
Section: A Validation Of the Experimental Proceduresmentioning
confidence: 99%
“…In order to validate the high pressure cell and the measurement technique, we measured the refractive index of three different pure fluids (toluene, hexane, and water, which refractive indices as a function of pressure are given in literature [29][30][31] ) as a function of pressure in the range from atmospheric pressure up to 50 MPa. In Fig.…”
Section: A Validation Of the Experimental Proceduresmentioning
confidence: 99%
“…For liquids, dn/dT has to be experimentally determined. In the case of water, Harvey et al [6] reported the refractive index at different wavelength in the visible spectrum, versus pressure and temperature. A fitting of data, at the atmospheric pressure and averaged over the visible wavelength range, gave n 0 = 1.335 (at 20°C) and the following relationship of dn/dT with T in the 15-40°C range…”
Section: Introductionmentioning
confidence: 99%
“…1͑a͒. The most important insights from this analysis lie not in the quality of the fit ͑which is high, 2 ϭ0.24ϫ10 Ϫ10 ͒ nor in a detailed comparison with the fitting function of Harvey et al 9 which was required to address a much broader range of temperature, pressure, and wavelength conditions. Rather, the value of the mixture model approach is revealed in Figs.…”
mentioning
confidence: 99%
“…10 We focus on the Saubade data because it covers the particularly interesting temperature range where the refractive index has a local maximum making the physical consequences of the mixture model most apparent. To compare with the refractive index fitting function of Harvey et al 9 the IPTS-68 temperatures were converted to their ITS-90 equivalents 12 and the results are plotted in Fig. 1͑a͒.…”
mentioning
confidence: 99%
See 1 more Smart Citation